2018
DOI: 10.3389/fnins.2018.00733
|View full text |Cite
|
Sign up to set email alerts
|

The Endocannabinoid System and Oligodendrocytes in Health and Disease

Abstract: Cannabinoid-based interventions are being explored for central nervous system (CNS) pathologies such as neurodegeneration, demyelination, epilepsy, stroke, and trauma. As these disease states involve dysregulation of myelin integrity and/or remyelination, it is important to consider effects of the endocannabinoid system on oligodendrocytes and their precursors. In this review, we examine research reports on the effects of the endocannabinoid system (ECS) components on oligodendrocytes and their precursors, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 133 publications
0
40
1
4
Order By: Relevance
“…The CB1R also regulates neural progenitor cell fate decisions, as evidenced by its involvement in the differentiation of neural progenitor cells toward an astroglial lineage [ 240 ]. Interestingly, both CB1Rs and CB2Rs have been shown to regulate oligodendrocyte progenitor cells function, via a PI3K/AKT pathway, whereby their activation exerts a protective role [ 81 , 241 ]. Although the role of CB2R in CNS development is not as well studied, there is evidence of its involvement in neural progenitor cell proliferation, and possibly in neurogenesis [ 242 ].…”
Section: Biological Role Of the Cannabinoid Receptorsmentioning
confidence: 99%
“…The CB1R also regulates neural progenitor cell fate decisions, as evidenced by its involvement in the differentiation of neural progenitor cells toward an astroglial lineage [ 240 ]. Interestingly, both CB1Rs and CB2Rs have been shown to regulate oligodendrocyte progenitor cells function, via a PI3K/AKT pathway, whereby their activation exerts a protective role [ 81 , 241 ]. Although the role of CB2R in CNS development is not as well studied, there is evidence of its involvement in neural progenitor cell proliferation, and possibly in neurogenesis [ 242 ].…”
Section: Biological Role Of the Cannabinoid Receptorsmentioning
confidence: 99%
“…However, it clearly demonstrated that the exogenous administration of 2‐AG ameliorated both acute and chronic disease models, with a significant impact on acute relapse severity and chronic progressive disability, and a reduced mortality rate in severe MOG‐EAE. Not only the administration of exogenous 2‐AG but also increased levels of this neurotransmitter due to the blockade of its main catabolic enzyme, namely MAGL, exerted positive effects on oligodendrocyte excitotoxicity and helped preventing demyelination in vivo [111,139] . MAGL plays a pivotal role in the regulation of 2‐AG levels and its pharmacological inhibition could contribute to protect neurons from pro‐inflammatory and excitotoxic stimuli, through the activation of CBRs [140,141] .…”
Section: Magl Inhibitors In Msmentioning
confidence: 99%
“…Concomitantly, in MS there is myelin damage and oligodendrocyte loss, and thus, finding new mechanisms to promote both re-myelination and OPC differentiation, either from precursors present in the brain parenchyma or derived from SVZ NSCs is crucial, since OPCs are able to migrate and partially remyelinate lesioned areas [249,419,420,421]. Cells from the oligodendroglial lineage are directly modulated by cannabinoids in distinct maturation stages, ranging from the regulation of OPC survival, proliferation, migration and differentiation to the modulation of mature oligodendrocyte survival and myelinating capacity [422,423]. For instance, it has been observed that OPCs express CB1Rs and CB2Rs and that cannabinoids promote OPC survival and oligodendrocyte differentiation through the PI3K/Akt/mTORC1 signaling pathway, which is known to participate in the myelination process [229,231,422,424,425,426,427,428,429].…”
Section: Role Of Cannabinoids In Neurogenesis and Pathophysiologymentioning
confidence: 99%